PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DENGAN DISIPLIN SEBAGAI VARIABEL INTERVENING - Deni, Rama; Heliyani, Heliyani (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2020)
ABSTRACTThis study aims to analyze and test the effect of compensation and work confusion on employee performance with discipline as an mediasi variable. This research was conducted at the Lima Puluh Kota Regional Secretariat with a type of comparative causal research. The population in this study was ASN who served in the Lima Puluh Kota Regional Secretariat totaling 118 people. Data is processed using Structural Equation Modeling (SEM) with the Smart PLS application. The results showed that: Compensation, positive and not significant effect on employee performance, the work environment had a positive and significant effect on employee performance, discipline had a positive and significant effect on employee performance, Compensation had a positive and significant effect on employee discipline, the work environment had a positive and significant effect. significant on employee discipline, Compensation on employee performance with disciplinary inter mediaries positive influence is not significant on employee performance, work environment on employee performance with disciplinary inter mediaries positive influence, and significant on employee performance at the Lima Puluh Kota Regional SecretariatKeywords: Compensation, Work Environment, Discipline, Employee Performance